Short-Term Exercise Approaches on Menopausal Symptoms, Psychological Health, and Quality of Life in Postmenopausal Women - Ayşegül Ağıl; Faruk Abıke; Arzu Daşkapan; Rıdvan Alaca; Handan Tüzün (Obstetrics and Gynecology International)
Objective. This study was designed to determine the effects of different short-term exercise programs on menopausal symptoms, psychological health, and quality of life in postmenopausal women. Material and Methods. Forty-two women were chosen from volunteering postmenopausal women presenting to the Department of Obstetrics and Gynecology of Bayındır Hospital between March and December 2009. The women aged 45–60 years and experiencing menopause naturally were included in the study. They were randomly divided into aerobic (𝑛=18) and resistance (𝑛=18) exercise groups. The women exercised 3 days per week for 8 weeks under the supervision of a physiotherapist. Aerobic exercise training was performed through a bicycle ergometer. Before and after the training, lipid profiles were measured and menopausal symptoms, psychological health, depression, and the quality of life were assessed through questionnaires. Results. In both exercise groups, no significant changes in lipid profiles were observed. In the resistance exercise group, excluding the urogenital complaints, there were significant improvements in all subscales of Menopausal Rating Scale (MRS). In the resistance exercise group, excluding the phobic anxiety, there were significant improvements in all subscales of The Symptom Checklist. Depression levels significantly decreased in both groups. Improvements were observed in all subscales of menopause-specific quality of life questionnaire in both groups except for sexual symptoms. Conclusion. Resistance exercise and aerobic exercise were found to have a positive impact on menopausal symptoms, psychological health, depression, and quality of life.